Ceratonia siliqua L. (immature carob bean) inhibits intestinal glucose absorption, improves glucose tolerance and protects against alloxan‐induced diabetes in rat. (11th November 2016) - Rtibi, Kaïs; Selmi, Slimen; Grami, Dhekra; Saidani, Khouloud; Sebai, Hichem; Amri, Mohamed; Eto, Bruno; Marzouki, Lamjed
Abstract: BACKGROUND: This study was designed to investigate the effects of immature carob pod aqueous extract (ICPAE) on intestinal glucose absorption in vitro and in vivo using an oral glucose tolerance test (OGTT) as well as the potential antidiabetic effect in alloxan‐induced diabetic rats. OGTT was carried by administration of glucose (2 g kg −1, p.o.) and after treatment with extract (50, 100 and 200 mg kg −1 body weight). Diabetes was induced by single intraperitoneal injection of alloxan (150 mg kg −1 ). However, the extracts at various doses or glibenclamide (GLB, 10 mg kg −1 body weight) were given by oral administration for 2 weeks. RESULTS: ICPAE (50–2000 µg mL −1 ) exerted dose‐dependent reduction of sodium‐dependent glucose transport across isolated mice jejunum and the maximal inhibition exceeded 50%.The ICPAE treatment improved glucose tolerance. More importantly, ICPAE at various doses showed a significant reduction in blood glucose and biochemical profiles in diabetic rats. CONCLUSION: Our findings confirm that the degree of maturity of carob characterized by a different phytochemical composition may be responsible for these actions. Therefore, these compounds may be used as a food supplement in hyperglycemia and diabetes treatments. © 2016 Society of Chemical Industry